Pengembangan Sumber Daya Manusia terhadap Kinerja Karyawan di PT. Bubuhan Multi Sejahtera Sungai Buluh Kabupaten Batang Hari - Etty Siswati; Niki Kosasi; Evi Fauzani; Rts Harta Delima; Fakarhan Hendra Putra (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study is to determine the effect of Human Resource Development on employee performance at PT, Bubuhan Multi Sejahtera Sungai Buluh Kabupaten Batang Hari Quantitative descriptive research method, data collection method using a questionnaire with a sample of 35 respondents and data analysis tool using a Likert scale. The results of the research show that Employee Education and Training in PT. Bubuhan Multi Sejahtera Sungai Buluh Kabupaten Batang Hari on employee performance, namely: partially the Education variable (X1) has no effect on employee performance with a t count of 0.821 <t table of 1.60389, for variables Training variable (X2) in PT. Bubuhan Multi Sejatera Sungai Buluh has an influence on employee performance t value 1.747> t table 1.60389. Taken together the variable Education and Training in PT..Bubuhan Multi Sejahtera Sungai Buluh Kabupaten Batang Hari has an influence on employee performance with a calculated F value of 3.663 > F tabeL 3.29 means